NATALE NATALE O, words and music by Father F. Giorgietti, F.S.C., Editrice Nigrizia, via Meloncello 3/3, Bologna, Italy, 19 pp. Zande text with an alternative Latin version - Basil, Brother (International Library of African Music, 1960)
pages: 79
Keywords: African Music